MEMBANGUN MODEL BERNEGOSIASI DALAM TRADISI LARANGAN-LARANGAN PERKAWINAN JAWA - Miftahul Huda (Sayyid Ali Rahmatullah Tulungagung State Islamic University, 2017)
This paper seeks to explore the model of negotiating the five families of Nahdliyyin-Muhammadiyah to the Ponorogo community over the traditional dispute over the prohibitions of Javanese marriage. The traditions of the Javanese marriage that is “weton”, “ngalon-ngulon”, “Golan-Mirah”, marriage of “lusan” and “madep-ngarep” marriage. Excavation model of the negotiation result is divided into three models. First, the model of negotiating within the frame of kalam (theology) and adat (tradition) connections the nappears to be incompatibility and inconsistency between the two. This is due to the emergence of different assumptions due to syirik (belief in more than of God) stereotype, because it is more holding the tradition than the existing of religious rules. Second, the model of negotiating within the framework of the Jurisprudence and adat connections that gave birth to the relationship of proximity and flexibility in responding to Javanese marriage customs or traditions so that it can be an alternative pattern of settlement. Third, the model negotiates within the framework of wisdom and diversity of customs/traditions. In the category of this meaning, the problem of the tradition of the prohibitions on Javanese marriage can be resolved by returning to the wisdom and diversity of tradition. Let the tradition solve itself. It seems that with this category the negotiation process goes fluently.